ANALYTICAL STUDY OF PANCHSHARA RASA THROUGH XRD, SEM, EDX AND ZP - Pawan, *Rajput; Shalini, Parashar; Ch, Sridurga (International Journal of Ayurveda and Pharma Research, 2016)
Rasa Shastra is a branch of medicine, which deals with preparation of the drugs with metals and minerals having wide range of therapeutic efficacy, possessing innate qualities like quick action, low dose, tastelessness, prolonged shelf life and better palatability. Panchshara Rasa (PSR) is one such Rasoushadhi mentioned in Bhaishajya Ratnavali, indicated in Shukrakshaya. Parada, Gandhaka and Shalmali moola (swarasa) are the main ingredients of PSR. Shodhana, Mardana, Bhavana and Parpati nirmana are the important steps involved in preparation of Panchshara Rasa. PSR is the blend of Kharaliya and Parpati Rasayana. In the current study of PSR was analyzed through X-ray diffraction (XRD), Scanning electron microscope (SEM), Energy dispersive X-ray analysis (EDX) and Zeta potential (ZP). XRD of PSR reveals that major peaks are of HgS (Meta cinnabar) compound. SEM study found the smallest grain size in ranging between 467.8 nm to 547.2nm at 7K magnification. EDX study reveals that PSR contains Hg-48.06%, S-38.42%, O-13.52% w/w. PSR shows ZP mean value is -37.4 mV which indicates moderate colloidal stability. The detailed Analytical study (i.e. XRD, SEM, EDX and ZP) of Panchshara Rasa will be discussed in the full paper.